Role of malaria exposure and off-target responses on RTS,S/AS02A vaccine immunogenicity and protection in Mozambican children - Elisa Fuentes; Chenjerai Jairoce; Didac Macià; Leonie Mayer; Jorge P. Torres-Yaguana; Marta Vidal; Rebeca Santano; David L. Narum; David Cavanagh; Benoit Gamain; Ross L. Coppel; James G. Beeson; et al. (npj Vaccines)
Abstract RTS,S/AS01E is the first malaria vaccine implemented for young African children. However, it provides partial protection against Plasmodium falciparum (Pf) malaria, and a better understanding of the mechanisms and determinants of vaccine immunity will help develop second-generation improved vaccines. We measured IgG to vaccine target and Pf blood-stage off-target proteins before and after vaccination in 874 children aged 1–4 years in a phase 2b trial of RTS,S/AS02A in Mozambique. We found that naturally acquired PfCSP IgG levels pre-vaccination were positively associated with RTS,S immunogenicity. Increased levels of IgG to the C-terminus and NANP-repeat regions of PfCSP, and to PfMSP5 and PfMSP1 block 2, following vaccination, were significantly associated with a lower hazard of clinical malaria over 6 months. Thus, immune priming, anti-PfCSP C-terminus and off-target antibody responses contributed to malaria protection after adjusting for prior Pf exposure, and this could guide strategies for optimizing the immunogen and vaccine deployment.